2007
DOI: 10.1073/pnas.0705582104
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of myofibroblasts from immune surveillance: A mechanism for tissue fibrosis

Abstract: Tissue fibrosis evolving from impaired tissue remodeling after injury is characterized by myofibroblast accumulation. We propose that during the development of fibrosis myofibroblasts acquire an immune-privileged cell phenotype, allowing their uninterrupted accumulation. Using the murine model of bleomycin-induced lung fibrosis in mice, we show that myofibroblasts that accumulate in lungs with fibrosis, but not in normal lungs, kill Fas ؉ lymphocytes, resist Fas-induced apoptosis, and survive longer when graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 41 publications
3
104
3
Order By: Relevance
“…Two recent studies have shown a similar sensitizing effect of PGE 2 on Fas-induced fibroblast apoptosis (14,21). Although the source(s) of Fas ligand (FasL) are not completely known, recent studies have suggested that myofibroblasts themselves may be an important source in the fibrotic lung (22,23). Taken together, these findings suggest that fibroblast and myofibroblast accumulation in the lungs of IPF patients could occur as a result of impaired sensitization to Fas-induced apoptosis.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Two recent studies have shown a similar sensitizing effect of PGE 2 on Fas-induced fibroblast apoptosis (14,21). Although the source(s) of Fas ligand (FasL) are not completely known, recent studies have suggested that myofibroblasts themselves may be an important source in the fibrotic lung (22,23). Taken together, these findings suggest that fibroblast and myofibroblast accumulation in the lungs of IPF patients could occur as a result of impaired sensitization to Fas-induced apoptosis.…”
supporting
confidence: 53%
“…Soluble FasL has also been detected in the bronchoalveolar lavage fluid of patients with a variety of interstitial lung diseases including IPF (52,53). Previous studies have shown FasL to be expressed by monocytes, macrophages, and NK cells (54,55), and recent studies have suggested that myofibroblasts themselves are an important source of cell-surface FasL (22,23). Myofibroblast expression of FasL has been implicated in epithelial injury in mice following intratracheal instillation with bleomycin (22,56), and epithelial cell apoptosis in IPF patients is often seen in areas overlying fibroblastic foci (56).…”
Section: Discussionmentioning
confidence: 99%
“…24,92 The indispensable role of the immune system in resolving fibrosis is highlighted by studies from Wallach-Dayan et al, 93 who demonstrated myofibroblasts from mice receiving bleomycin-induced lung fibrosis resist lymphocytic Fas-induced apoptosis and survive longer when grafted into allogeneic mice. These findings support the importance of specific immune surveillance of lung myofibroblasts in the resolution of fibrosis.…”
Section: Role Of Inflammatory Cells In Lung Fibrosis Resolutionmentioning
confidence: 99%
“…This escape from immune surveillance consolidates myofibroblast recruitment, and sustains fibrosis. 6,58 Watson et al 50 reported on the antiapoptotic effect of increased levels of NF-jB in liver fibrosis myofibroblasts, an additional mechanism that can prolong their survival.…”
Section: Characterization and Origin Of A Myofibroblastmentioning
confidence: 99%